The princess bride [videorecording (DVD)] - Reiner, Rob; Elwes, Cary, 1962-; Patinkin, Mandy; Wright, Robin, 1966- (MGM Home Entertainment, 2001)
A kindly grandfather sits down with his grandson and reads him a bedtime story. As the grandfather reads the story, the action comes alive in a classic tale of love and adventure. The beautiful Buttercup is kidnapped and held against her will in order to marry the nasty Prince Humperdinck, while Westley (her childhood beau, now returned as the Dread Pirate Roberts) attempts to save her. Along the way he meets an accomplished swordsman and a giant, both of whom become his companions in his quest.